EFEKTIVITAS MUSIK KLASIK DALAM MENURUNKAN KECEMASAN MATEMATIKA (MATH ANXIETY) PADA SISWA KELAS XI - Winja Susanti, Devi; Ainur Rohmah, Faridah (HUMANITAS (Jurnal Psikologi Indonesia), 2011)
This study aims to determine the effectiveness of classical music inreducing math anxiety. The participants in this study were 14 public highschool students from class XI at Department of Social Sciences (IPS)which has an average to above average IQ scores and high to very highlevels of anxiety. Data collection tool used Mathematics Anxiety Scaleand Evaluation Music Sheet. This study used a pretest-posttest experimentalwith control group design. Random used in this study was a matchingsystem. Data analysis in this study used Wilcoxon test. The results of dataanalysis showed significant decrease in scores between pretest and posttestin the experimental group (KE) with p = 0.014. This result indicated thatclassical music was effective in reducing math anxiety in students. Mathanxiety might decline as the students listen to classical music while learningmathematics.